Protonation of histidine 55 affects the oxygen access to heme in the alpha chain of the hemoglobin from the Antarctic fish Trematomus bernacchii. - Boechi L.; Martì M. A.; Estrin D. A.; VERGARA, ALESSANDRO; SICA, FILOMENA; MAZZARELLA, LELIO; MERLINO, ANTONELLO (IUBMB Life, 2011)
The Root effect describes the drastic drop of oxygen affinity and loss of cooperativity at acidic pH expressed in the hemoglobins (Hb) of certain fish. The comparison between the deoxy structures of the Root effect Hb from the Antarctic fish Trematomus bernacchii (HbTb) at different pHs (pH = 6.2 and pH = 8.4) shows that the most significant differences are localized at the CDα region, where a salt bridge between Asp48 and His55 breaks during the low-to-high pH transition. In order to shed light on the relationship between pH, CDα loop structure and dynamics, and oxygen access to the active site in the alpha chain of HbTb, different computer simulation techniques were performed. Our results highlight the importance of the protonation of His55 in regulating oxygen access, underscoring its pivotal role in the structural and functional properties of HbTb. These data provide further support to the hypothesis that this residue might contribute to the release of Root protons in HbTb and underline the fact that an efficient transport of molecular oxygen in Hbs relies on a subtle balance of tertiary structure and protein conformational flexibility.